Thermodynamic Performance Analysis of Human Cardiovascular System for Normal and Cardiomegaly Conditions - Dutta, Abhijit; Chattopadhyay, Himadri; Çatak, Jale; Çatak, Jale (World Scientific, 2022)
This study aims to determine the thermodynamic performance of the cardiovascular system for healthy and cardiomegaly conditions where work done by the heart and lung is considered as input expenses. Analysis based on the second law of thermodynamics was performed under three distinct physiological conditions: resting, moderate, and excessive activity levels. From this analysis, it is noted that, exergy transfer rate increases with the increase in the physiological activity level. The exergetic efficiency of the cardiovascular system is about 55% at resting and changes by about 4% with physical activity level. The human cardiovascular system efficiency is increased with an increase in breathing air inlet temperature and relative humidity irrespective of physiological conditions. The work also quantifies the efficiency of the heart and lung as individual systems. For a fixed breathing air inlet temperature and relative humidity, the cardiovascular system performance increases with a decrease in physical activity levels.
Keywords: Cardiomegaly; Cardiovascular system; Efficiency; The second law of thermodynamics; Thermodynamic performance